Comparison of clinical and immulogical responses to Zidovudine (AZT) and Tenofovir (TDF) – containing ARV regimens in patients taking HAART at Roma health service area of Lesotho - Adebanjo, Adefolarin Babafemi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMed) -- Stellenbosch University, 2010.